Validation of Shoemakerella fissipro Ortiz, Capetillo & Winfield, from the Gulf of California, northeastern Pacific Ocean (Amphipoda: Amphilochidea: Lysianassidae) - Ortiz, Manuel; Capetillo, Norberto; Winfield, Ignacio (Zootaxa, 2020)
Ortiz et al. (2018) described a new species of lysianassid amphipod, Shoemakerella fissipro, from Gulf of California, northeastern Pacific Ocean. Although the description and figures presented by Ortiz et al. (2018) fully characterize the new species, the journal issue in which the description appeared was published online only, and the article in which the new name appeared did not include a ZooBank registration number (LSID), required for validation of new names in electronic-only publications (ICZN 2012). As a result, the name Shoemakerella fissipro Ortiz, Capetillo & Winfield, 2018, as published in Cahiers de Biologie Marine 59: 599–605, is not available according the International Code of Zoological Nomenclature (ICZN 1999, 2012). Therefore, the present note serves to validate name Shoemakerella fissipro by fulfilling ICZN conditions for nomenclatural availability.